Objective and Social Factors as Determinants of Task Perceptions and Responses: An Integrated Perspective and Empirical Investigation - Griffin, Ricky W.; Bateman, Thomas S.; Wayne, Sandy J.; Head, Thomas C. (Academy of Management Journal, 1987)
The purpose of this study was to test the merits of an integrated perspective derived from the job characteristics and social information processing models of task design. We conducted a complex laboratory study, manipulating objective properties of a task, social information, and changes in both. Results suggested strong support for the integrated perspective. Implications for future theory and research are discussed.